Peningkatan Pengetahuan dan Kesadaran pada Anak dalam Pencegahan dan Pengendalian Covid-19 dengan Buku Permainan Mazzle - Faiyana Nurul Arrifqi; Intan Dyah Prawesti; Thalia Diva Prameswari; Safira Restiara Dyah Palupi; Yuni Tri Widyastuti; Dewi Yuniasih (Universitas Pahlawan Tuanku Tambusai, 2021)
Covid-19 does not only attack adults, but all ages including children. The total number of Covid cases in children under the age of 10 in the Yogyakarta area has reached 4,723, but there has been no special counseling aimed at children in this regard. Therefore, this community service aims to provide socialization and counseling about Covid-19 and Health protocols in handling and preventing Covid-19. This community service activity has been in the Family Planning Village, Kintelan, Bambanglipuro Bantul. This activity was carried out offline and online for 3 socializations, starting at 08.00 WIB until 11.00 WIB. The number of participants who attended was 20-30 children aged 4-7 years. The outputs produced according to the planned community service activity are increasing children's knowledge about Covid-19 and 5M and the implementation of the health protocol.